PENERAPAN METODE DRILL DALAM MENINGKATKAN KETERAMPILAN MEMBACA NOTASI ANGKA PADA PEMBELAJARAN PIANIKA - Nurmansyah, Nurmansyah; Syahrani, Agus; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to implementing drill method can improve students in reading skill of the notation numbers on pianica learning. This research used descriptive methods, with the qualitative approach. The research method applied is a classroom action research with the cycle of planning, acting, observing, and reflecting. The subject of this research is class VII especially class VII B of SMPN 2 Sambas. Data collecting that are applied in this research are data learning process and the students in reading skill of the notation numbers. The results of this research show that the application of the drill method can be improved students skill in reading notation numbers on learning pianica. The result can be seen from the percentage of completeness in cycle 1 and cycle 2. The mastery percentage of students there is an increase from 64.10% to 89.74%.Â Keywords:Â Drill Method, Notation Numbers, Learning Pianica